Representation and a Religious Pressure Group: An Examination of the Baptist Joint Committee on Public Affairs - Peterson, Walfred H. (A journal of church and state, 1973)
Walfred H. Peterson; Representation and a Religious Pressure Group: An Examination of the Baptist Joint Committee on Public Affairs, Journal of Church and State